2015
DOI: 10.1590/01000683rbcs20140521
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Loss by Erosion From Mechanically Tilled and Untilled Soil Under Successive Simulated Rainfalls

Abstract: the description of the fate of fertilizer-derived nitrogen (N) in agricultural systems is an essential tool to enhance management practices that maximize nutrient use by crops and minimize losses. soil erosion causes loss of nutrients such as N, causing negative effects on surface and ground water quality, aside from losses in agricultural productivity by soil depletion. studies correlating the percentage of fertilizer-derived N (fdN) with soil erosion rates and the factors involved in this process are scarce.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Little is known about how the loss of soil, nutrients, and agricultural productivity has changed over the years in the Cerrado [32][33][34][35][36][37]. Some studies of soil loss have been made on the medium to small scale or in plots [32,33,[35][36][37]; however, they do not give an overview of degraded soils in a large ecosystem scale or point out the main activities that cause soil degradation. Studies which consider a geospatial analysis, including applications using GIS, remote sensing, and the RUSLE model are sparse and cover limited areas within the Cerrado.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about how the loss of soil, nutrients, and agricultural productivity has changed over the years in the Cerrado [32][33][34][35][36][37]. Some studies of soil loss have been made on the medium to small scale or in plots [32,33,[35][36][37]; however, they do not give an overview of degraded soils in a large ecosystem scale or point out the main activities that cause soil degradation. Studies which consider a geospatial analysis, including applications using GIS, remote sensing, and the RUSLE model are sparse and cover limited areas within the Cerrado.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies exist on the potential decrease in productivity caused by water erosion [38]. Additionally, little data exists on nutrient dynamics in eroding landscapes, despite the importance of nutrients for primary production [35]. Therefore, taking into account those reasons and addressing the challenge of food security, soil degradation, and the importance of the Cerrado for meeting future agricultural production, the main goal of this study is to obtain an overview of the loss of soil, agricultural productivity, and nutrients caused by water erosion in the Brazilian Cerrado between 2000 and 2012.…”
Section: Introductionmentioning
confidence: 99%
“…However, soil management can significantly influence the soil nitrogen loss. Bramorski et al (2015) reported that the absence of soil tillage led to higher soil erosion and higher total nitrogen losses mainly in organic form and associated with the finer soil minerals. On the other hand, the losses of fertiliser-derived N from tilled soil plots were higher.…”
Section: Soil Categorisation From the Point Of View Of Water Source Pmentioning
confidence: 99%
“…It is reported that nitrogen fertilizers are lost greatly from tilled soil plots, and the intensity of the rains impact the soil losses quantity. The nitrogen fertilizers losses were less on untilled plots [24]. Soluble nutrients such as nitrate and potassium can be lost in runoff and drainage water, whereas less soluble nutrients such as phosphorus can be lost with sediments moving in eroding soil and runoff water [25].…”
Section: Fertilizers Losses By Soil Erosionmentioning
confidence: 99%